The Review Of Agricultural Land Transfer Related Juridical Absentee That Made Before PPAT - Heris Ramadan; Sumaryono Sumaryono (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study as follows 1) To identify and explain the transfer of agricultural land Absentee made before PPAT. 2) To identify and explain the barriers and solutions Absentee transfer of agricultural land made before PPAT. The method used by researchers is sociological approach juridical law and specification in this study were included descriptive analysis. The source and type of data in this study are primary data obtained from field studies with interview, and secondary data obtained from the study of literature. Based on the results of the research are Strict monitoring of the transfer of agricultural land through cooperation between the relevant agencies, namely the Village Head, District and PPAT / Notary. Barriers: a) Lack of public awareness, b) Since the Inheritance Land where many families who left their land to her son while her son stayed in town and have settled the town even had a decent job in the city than in the rural location of his land, it is also one causes of land ownership is due to inheritance. c) Land Office did not have accurate data on their ownership of agricultural land by Absentee. Solution: Perform legal counseling for the creation of legal order are carried out continuously to the community and local authorities with regard to land issues.Keywords: Judicial Review; Diversion; Farmland; Absentee; PPAT